Methodological fundamentals of the synthesis management system of quality of granting of services - Харченко, В.П.; Кучеренко, В.О.; Семенов, О.О. (Proceedings of National Aviation University (archive), 2005)
The methodological fundamentals of the synthesis of the Quality Management Systems are reviewed with the purpose of characteristics assurance of production in a master schedule pursuant to the requirements of the standards ISO of a series 9000.